Test The Attraction of Spodoptera exigua Imago To Several Traps on Shallot Crops - Retno Kusumawati; Betty Sahetapy; Sartje H. Noya (Faculty of Agriculture, Pattimura University, 2022)
The objective of the research was to find the effective traps fro trapping the imago of Spodoptera exigua Hbn. The research was conducted in Dusun Taeno Atas, Rumah Tiga Village, Teluk Ambon District, Central Maluku Regency, from September to December 2020. The study used shallot seeds cv. bauji. The treatments used were exi pheromone trap (PF), yellow trap + exi pheromone (PKF) and yellow trap (PK). The control treatment was without pheromone. The study used a completely randomized design (CRD) with three replications. The results showed that pheromone traps were the most effective for trapping Spodoptera exigua Hbn pests.